2011
DOI: 10.1159/000328915
|View full text |Cite
|
Sign up to set email alerts
|

Structural Heterozygosity, Duplication of Telomeric (TTTAGGG)<sub>n</sub> Clusters and B Chromosome Architecture in <i>Tradescantia</i> <i>virginiana</i> L.

Abstract: Fluorescent in situ hybridization, C-banding/DAPI, and CMA3-fluorescence were performed to reveal the cytomolecular constitution of the standard (A) and supernumerary (B) chromosomes of an autotetraploid Tradescantia virginiana L. The analyses show that translocations and/or inversions have occurred during the evolution of the T. virginiana karyotype, generating a significant level of structural heterozygosity. Regarding the structural level, the present paper confirms the occurrence of small subter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Another example concerning the presence of additional telomeric sequences in B chromosomes has been reported in the plant Tradescantia virginiana, where they emerged by small duplications or subterminal inversions. In addition, it has been suggested that the B chromosome originated by excision of the distal region of an A chromosome [Golczyk, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Another example concerning the presence of additional telomeric sequences in B chromosomes has been reported in the plant Tradescantia virginiana, where they emerged by small duplications or subterminal inversions. In addition, it has been suggested that the B chromosome originated by excision of the distal region of an A chromosome [Golczyk, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…To detect evolutionarily conserved 18S-5.8S-26S and 5S rDNA sites, a 2.3 kb ClaI fragment of the 26S rDNA ribosomal gene of A. thaliana (Unfried and Gruendler 1990 ) labeled with digoxigenin-11-dUTP (Roche Applied Science) by nick translation and the 5S rDNA coding unit, PCR-labeled with tetramethyl-rhodamine-5-dUTP (Roche Applied Science), were obtained as previously described (Golczyk 2011a ; Golczyk et al 2014 ) and used as probes.…”
Section: Methodsmentioning
confidence: 99%
“…A fluorescent version of C-banding, "C-banding/DAPI" (Golczyk, 2011b), was also conducted. Briefly, in contrast with the conventional C-banding method, after hot saline treatment (23 SSC at 60°C), the preparations were mounted in DAPI-Vectashield medium instead of staining in Giemsa-phosphate buffer.…”
Section: C-banding: Conventional Giemsa C-banding and C-banding/dapimentioning
confidence: 99%